Effect of Ecotype and Environment on Oil Content, Fatty Acid, and Sterol Composition of Seed, Kernel, and Epicarp of the Atlas Pistachio - Amina Labdelli; Mohammed Tahirine; Abdelhamid Foughalia; Kamel Zemour; Muriel Cerny; Ahmed Adda; Valérie Simon; Othmane Merah (Agronomy, 2022)
The Atlas pistachio fruits are an important source of food due to their high fat content and medicinal interest in arid lands. For a better use, it is necessary to understand the diversity and distribution of lipids in their fruit. The purpose of the present study is to determine oil content, fatty acid, and phytosterol composition using gas chromatography of three ecotypes in Algeria during two consecutive years. The seed oil contents ranged from 32 to 47.8% depending on both year and ecotype. Unsaturated fatty acids (FA) represent at least 71% of total FA. The fruit contains a considerable level of phytosterols. The highest level of oil content and unsaturated FA were observed in the fruit of Bechar regardless of the part of the fruit. The study indicated that oil quality of the Atlas pistachio seed varies according to genotype and environmental conditions, and the findings could help breeders for diversity and selection program management.